Developing Social-Emotional Learning (SEL) Competencies Through Cooperative Learning Strategies in the Classroom - Nurhayati Nurhayati; Aiman Fariq; Syafiq Amir (Yayasan Adra Karima Hubbi, 2025)
Social-Emotional Learning (SEL) has gained increasing attention as a critical component of holistic education that supports students’ academic success, well-being, and interpersonal competence. This study aims to examine the effectiveness of cooperative learning strategies in developing students’ SEL competencies within classroom settings. A quasi-experimental mixed-methods design was employed involving an experimental group exposed to structured cooperative learning activities and a control group receiving conventional instruction. Quantitative data were collected using standardized SEL questionnaires measuring self-awareness, self-management, social awareness, relationship skills, and responsible decision-making, while qualitative data were obtained through classroom observations and reflective student responses. The findings reveal significant improvements in overall SEL competencies among students participating in cooperative learning, with the strongest gains observed in relationship skills and social awareness, followed by self-management and responsible decision-making. Observational data corroborate these results by demonstrating enhanced peer interaction, emotional regulation, and a more supportive classroom climate. The study concludes that cooperative learning provides authentic social contexts that enable students to practice and internalize SEL competencies through structured interaction and shared responsibility. The novelty of this research lies in its integrative perspective that positions cooperative learning not only as an academic instructional strategy but as a deliberate and sustainable approach to SEL development embedded in everyday classroom practice.